ZDHHC5 may regulate the function of NKT cells and the immune response in Meniere’s disease - Ruilong Li; Keguang Chen (Mammalian Genome, 2026)
Meniere’s disease (MD) is a heterogeneous, rare inner ear disorder characterized by recurrent vertigo, fluctuating sensorineural hearing loss, tinnitus, and aural fullness. Its molecular mechanisms remain unclear due to significant clinical and immunological heterogeneity. In this study, we integrated multi‑omics genetic data to systematically screen for palmitoylation regulatory genes associated with MD risk. We first intersected 31 core palmitoylation genes with blood cis‑eQTL datasets to identify candidate expression‑related genes, then performed two‑sample Mendelian randomization (MR) to examine their genetic correlation with MD. Summary‑data‑based MR (SMR) using two independent peripheral blood eQTL cohorts (eQTLGen and GTEx) was further applied to validate robust candidate genes. Two‑sample inverse‑variance weighted (IVW) MR revealed nominally significant associations between PPT2, ZDHHC18, ZDHHC5 and MD risk. Independent SMR validation confirmed that peripheral ZDHHC5 expression was significantly correlated with MD (eQTLGen: PSMR = 0.023; GTEx: PSMR = 0.006), and a non‑significant HEIDI test ruled out strong linkage disequilibrium confounding. We further explored potential immune mediators using a two‑step MR screening framework covering 731 peripheral immune cell phenotypes. After Benjamini–Hochberg false discovery rate (FDR) correction for all immune traits to control for multiple testing, no immune cell phenotype retained an FDR